METODE PENDIDIKAN AQIDAH DALAM TRADISI PROPETIK NABI MUHAMMAD SAW - Akmansyah, M. (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2014)
The Islamic doctrine and beliefs (aqidah) is the importantcomponent of the Islamic education subject. Teaching the aqidahiscritical issue to give Muslims young generations convincinganswers to these world modern challengers. The main objective ofteaching Islamic doctrine should be to reinforce our youngMuslims with the intellectual and spiritual weapons that can standto the globalization. This research analyze and try to find theanswer of “What is the aqidah education for the children in theProphetic Hadith perspectives ?.”The study used the qualitative research approach thatexplore and research topics that require the research questions in detail. The study used the library research design where the data were collected through literatures analysis. The data were managed and analyzed using descriptive analysis research.This study found that the main objective of teachingaqidah is to produce the young Muslims generations that haveGod consciousness in all aspect of life. There are five basicmaterials in aqidah education based on the prophetic Hadith,teaching the word “la ilaha ila Allah”, planting the love Allah intheir soul and feel supervised by Him, planting the love ProphetMuhammad SAW and his family, teaching them the Qur'an, andeducating them to hold firmly the aqidah and will sacrifice for it.There are three basic principles used in Prophetic Haditson aqidah education: First, planting the correct aqidah, (byteaching the faith from early age, providing an explanation andassertion through parable method (matsal), using visual aid, thestory method and the question and answer method), and taking the advantage of every opportunity. Second, correcting the mistake by using the advice method, testing and strengthening their faith, (through reasoning and giving alternative, showing the mistake, and expressing anger), warning the impact, criticizing and punishment method. Third, keeping the children‟s faith by supporting them to hold firmly the al-Qur‟an and al-Sunnah, avoiding conflict areas (fitan), avoiding doubtful (syubhât) and maintaining their faith with good deed.